British Thoracic Society Quality Standards for outpatient management of pulmonary embolism. Issue 1 (18th August 2020) - Condliffe, Robin; Albert, Paul; Alikhan, Raza; Gee, Emma; Horner, Daniel; Hunter, Laura; Jacobs, Phillip; Limbrey, Rachel; Newnham, Michael; Preston, Wendy; Patel, Sheena; Smith, Laura-Jane; et al.
Abstract : Introduction: The purpose of the quality standards document is to provide healthcare professionals, commissioners, service providers and patients with a guide to standards of care that should be met for outpatient management of pulmonary embolism in the UK, together with measurable markers of good practice. Quality statements are based on the British Thoracic Society (BTS) Guideline for the Initial Outpatient Management of Pulmonary Embolism. Methods: Development of BTS Quality Standards follows the BTS process of quality standard production based on the National Institute for Health and Care Excellence process manual for the development of quality standards. Results: Six quality statements have been developed, each describing a standard of care for the outpatient management of pulmonary embolism in the UK, together with measurable markers of good practice. Discussion: BTS Quality Standards for Outpatient Management of Pulmonary Embolism form a key part of the range of supporting materials that the society produces to assist in the dissemination and implementation of a guideline's recommendations.